The Variational Principle for Entropy of Countable State Shift Spaces with Specification - Paschal, Alex; Somers, Amy (The PUMP Journal of Undergraduate Research, 2026)
We generalize the well-studied specification property to countable-state shift spaces. We present an infinite class of examples of such spaces. Using a generalized notion of Gurevich entropy, we prove the variational principle for these spaces. This lays the foundation for developing the theory of equilibrium states in this setting.